The Avignon Papacy Contested: An Intellectual History from Dante to Catherine of Siena - Falkeid, Unn (I Tatti Studies in Italian Renaissance History Ser, 2017)
Cover -- Contents -- Introduction -- 1. The Eagle's Flight: Dante's Paradiso VI and the Monarchia -- 2. Marsilius of Padua and the Question of Legitimacy -- 3. Individual Freedom in William of Ockham's Breviloquium -- 4. Petrarch, Cola di Rienzo, and the Battle of Rome -- 5. The Prophetic Widow: Birgitta of Sweden and the Revelaciones -- 6. Catherine of Siena and the Mystical Body of the Church -- Conclusion -- Chronology -- Notes -- Bibliography -- Acknowledgments -- Index.